Proceedings of the 38th Annual Hawaii International Conference on System Sciences
DOI: 10.1109/hicss.2005.445
|View full text |Cite
|
Sign up to set email alerts
|

Movie Review Mining: a Comparison between Supervised and Unsupervised Classification Approaches

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
161
1
1

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(164 citation statements)
references
References 6 publications
1
161
1
1
Order By: Relevance
“…They concluded that due to scarcity of words in movie reviews, it is hard to use bag-of-words features using supervised learning methods. Their results were 85.54 % for 3-fold cross validation and 66.27 % when applied on the test data set [4].…”
Section: Related Workmentioning
confidence: 66%
“…They concluded that due to scarcity of words in movie reviews, it is hard to use bag-of-words features using supervised learning methods. Their results were 85.54 % for 3-fold cross validation and 66.27 % when applied on the test data set [4].…”
Section: Related Workmentioning
confidence: 66%
“…Many datasets don't have all data' label information. The main problem is that gathering label information takes long time and costly process [5]. On the other hand, unlabeled data is easy to obtain and also plenty in literature for researchers.…”
Section: Active Sample Selection In Ensemble Learningmentioning
confidence: 99%
“…On the other hand, unlabeled data is easy to obtain and also plenty in literature for researchers. At this stage, clustering methods are used for unlabeled data classification which is known as unsupervised method in literature but success of the separation the data is low than supervised methods' success [5]. Recently, many studies are made on forming new classification models which is based on supervised techniques but use less labeled data in training process because of difficulty in obtaining [10], [11].…”
Section: Active Sample Selection In Ensemble Learningmentioning
confidence: 99%
See 2 more Smart Citations